Political Motives in Term of Criminal Definition on Terorism Law in Indonesia - Prayitno Imam Santoso; Abdul Kadir (Universitas Muhammadiyah Sidoarjo, 2019)
In Law Number 5 Year 2018, the definition of terrorism with political motives is regulated. This is different from the previous regulation, namely Law Number 15 Year 2003 concerning the stipulation of Government Regulations in lieu of Law Number 1 Year 2002 concerning Eradication of Terrorism Criminal Acts. The issue raised is how the political motives as the goal of terrorism and what are the fundamental changes of the latest terrorism law. This research uses normative legal research in which the study legal material contains normative rules. With the ratification of the Terrorism Law, political motives are used as an element of the offense formula. Some changes are on the Definition of Terrorism, Terrorism Organizations, Military and Paramilitary Training, Incitement, involvement of children, time of detention, arrest, wiretapping, protection, victims' rights, prevention, BNPT, TNI involvement and oversight by the DPR.